Breaking up, making out, and shaping up an analysis of the representations of women and men in Maya O. Calica's The Breakup Diaries using Halliday's Transitivity System - Juan, Gianina Rea V.C.; Ventura, Eloisa May P. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2004)
This study uses Halliday's Transitivity framework to analyze the representations of women and men in selected passages from a popular romance novel entitled The Breakup Diaries by Maya O. Calica. analyzing the characters form these passages according to the different process types they used brought about linguistic evidence of how different characters are represented in different ways. These representations showed how stereotypes and ideologies are incorporated in popular romance fiction. In this light, The Breakup Diaries was seen from a feminist perspective, showing how the representations of women and men can be used to serve or promote an oppressive ideology like patriarchy. This study demonstrates how language functions as a medium of representation, both of our outer world and inner consciousness. These are manifested through the different process types used by the different characters to represent themselves and their relationship with others.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.